PENGARUH PENGGUNAAN PARANET SEBAGAI PELINDUNG SEMENTARA TERHADAP PERTUMBUHAN TANAMAN KAKAO (Theobroma cacao, L) - Sukadi Sukadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
Plants cocoa to grow well need a tree protective while and tree protective remain. Preparation of the plants protection while and plants protection remain done during 12-18 months before the cocoa planted. Using paranet as a protective while can accelerate the time planting cocoa. This result was conducted in the experemintal BBPP Binuang for 13month of October 2016 until the month of December 2017.  Reach done by planting cocoa Hibrid F1 along with the installation of paranet individually and as well planting lamtoro protector remain.The result showed that growth in cocoa can grow well, at age month was formed jorket by the number of 5-6 branch, where in cut so that the remaining 3 branch symetric, average high jorket 109,6 centimeters from the ground.  Plants cocoa already flowering after the age of 13 months.